Ergonomic analysis of the physical space of the home office in teachers at federal institutes (Human Factors in Design, 2023)
The objective research of evaluating the physical space of the home office used by teachers, based on the domains of specialization of ergonomics and NR-17, justified by the current context of the pandemic that required a series of changes in the performance of their professional activities. Of an applied nature, with a qualitative approach and with exploratory and descriptive objectives, the study was developed in four phases: (1) data collection; (2) development and application of the questionnaire; (3) data analysis and treatment and (4) ergonomic contributions. As a result, it is understood that ergonomics can contribute to the strategic planning of educational institutions, whether in the face-to-face and distance modalities.
Keywords: physical ergonomics; teacher; home office; teleworking